PENGARUH PERBANDINGAN TANAH DAN KOMPOS DAUN BAMBU (Bambusa arundinacea) TERHADAP PERTUMBUHAN SEMAI TANJUNG (Mimusops elengi L) - Rusdi, Erwin; w, warda; y, Yusran; Wahyuni, Dewi (Jurnal Warta Rimba, 2019)
Bambusa arundinacea contains high of Phosporous and Potassium (P and K) elements, that have a high potential to be main material for compost. Both P and K are very importent in inproving soil quality and plant growth. The studywas conducted on January until march 2019 at Permanent Nursery of BPDAS Palu-Poso, Tadulako University, Central Sulawesi. The study was arranged by a Completely Randomized Design with four treatments, i.e. S0 = soil without bamboo leave compost; S1= 300 g soil : 300 g compost; S2 = 400 g soil : 200 g compost; S3 = 450 g soil : 150 g compost. Each treatment are replicated on 7 replications. There are 28 experimental units. Growth parametres observed are seedling height, stem diameter and number of leaves, wet and dry weight of shoots and roots of seedlings, and seedling quality index. Result of study showed that bamboo leave compost significantly effect on Mimusops elengi L seedling growt. Treatment S2 = 400 g soil : 200g compost might significantly increase tanjong tree seedling growth, as follows seedling height growth (4,16 cm), stem diameter (0,3 mm), leave numbers (3 leaves), shoot wet weight (1.36 g), root wet weight (0.26 g), shootdry weight (0.53 g), root dry weight (0.22 g), and seedling quality index of 0,05.